REFLECTIVE READING JOURNAL IN TEACHING WRITING - Yanuarti Apsari (University of Kuningan, 2018)
A number of studies suggested that journal writing is a supportive tool that encourages learners’ reflective activity and that reflective thinking skills can be taught and learned. Accordingly, this study investigated the implementation of reflective reading journal in teaching writing as well as the benefits that the students obtained after writing reflective reading journal. This study employed a case study research design which used three data collection including observation, interview and students’ texts. The results of the study revealed that reflective reading journal can be used effectively to improve students’ writing skill through several ways. First, the students were required to produce clearly defined paragraphs which include two sections. The first section included referencing data, such as author and title, and a paraphrase of the reading. The second section contained a response to a specific aspect of the reading. Second, the participants of the research were involved in decision making of topics for reading. Third, they wrote reflective reading journal weekly. Fourth, teacher gave feedback to students’ journal entries. In addition,the study also showed that there were some benefits, namely development of ideas, improvement of textual coherence, and Improvement of textual cohesion.Keywords: reflective reading journal; writing; benefit; EFL; ELT.